On the Basis Property in Lp( 0,1) of the Root Functions of Non-self Adjoint Sturm-Lioville Operators (European Journal of Pure and Applied Mathematics, 2010)
In the present paper, we prove the basisness of the root functions of the non-self adjoint Sturm-Liouville operators with periodic and anti-periodic boundary conditions in space Lp(0,1), p>1. Here we assume that the potential is absolutely continuous in [0,1].